Engineering an atomic-level crystal lattice and electronic band structure for an extraordinarily high average thermoelectric figure of merit in n-type PbSe - Ge, Bangzhi; Lee, Hyungseok; Im, Jino; Choi, Youngsu; Kim, Shin-Yeong; Lee, Ji Yeong; Cho, Sung-Pyo; Sung, Yung-Eun; Choi, Kwang-Yong; Zhou, Chongjian; Shi, Zhongqi; Chung, In (Royal Society of Chemistry, 2023)
We stabilize multiscale defect structures involving interstitial Cu, displaced Pb and Se atoms from the regular lattice points, dislocations prompted by scarce anion vacancies, and nanoscale mosaics driven thermodynamically by the new composition CuxPb(Se0.8Te0.2)(0.95) (x = 0-0.0057). Directly observing their atomic-resolution structures, employing a spherical aberration-corrected scanning transmission electron microscope and atom probe tomography, uncovers formation mechanisms, helping understand how they affect bulk transport properties. They independently manipulate the physical quantities determining the thermoelectric figure of merit, ZT. Carrier concentration dynamically boosts electrical conductivity with rising temperature while negligibly damaging carrier mobility. The significantly increased effective mass of electrons in the conduction band above the theoretical prediction gives a high magnitude of Seebeck coefficients. Consequently, the best composition achieves a remarkably high average power factor of & SIM;24 & mu;W cm(-1) K-2 from 300 to 823 K, with a substantially depressed lattice thermal conductivity of & SIM;0.2 W m(-1) K-1 at 723 K. With a ZT of & SIM;0.55 at 300 K, an average ZT is & SIM;1.30 from 400 to 823 K, the highest for all n-type polycrystalline thermoelectric systems including PbTe-based materials. The achievement in this work greatly escalates the predictability in designing defect structures for high thermoelectric performance, and demonstrates that PbSe can eventually outperform PbTe in thermoelectrics.